The Protection of Islamic Women in Indonesia: Evaluation of Polygamy Sanctions and Its Implications - Firdaus, Firdaus; Desminar; Syaflin Halim; Mursal; Naska, Isral (Universitas Islam Negeri Madura, 2023)
The background of polygamy in Indonesia involves complexity in protecting women, especially economic, social, and psychological disparities. The practice of polygamy reflects the uncertainty of marriage and divorce regulations, giving rise to negative impacts on women and children, including conflict and domestic violence. The protection of women requires legal reform, an educational approach, and active community involvement to overcome injustice in the practice of polygamy. This research aims to understand the phenomenon of women's protection in the context of polygamy in Indonesia with a focus on the city of Padang. Primary data was collected through interviews and observations using qualitative descriptive methods, while secondary data from various literature reviews was analyzed using data description and conclusion-drawing techniques. Women who are polygamous face verbal, nonverbal, and physical pressure. Even though there are religious and legal regulations, the effectiveness of sanctions in Indonesia is still low. Solutions include education, unconditional denial of consent, and legal protection, while spiritual experts face challenges resulting from societal misunderstanding and intimidation from prospective husbands.